Seeds Act and Federal Plant Varieties Act and transgenic maize in Mexico - Espinosa-Calderón, Alejandro; Turrent-Fernández, Antonio; Tadeo-Robledo, Margarita; San Vicente-Tello, Adelita; Gómez-Montiel, Noel; Valdivia-Bernal, Roberto; Sierra Macías, Mauro; Zamudio-González, Benjamín (Revista Mexicana de Ciencias Agrícolas, 2018)
This paper reviews the process that has occurred in Mexico around seed laws, especially the law of seed (2007) and the proposed new Federal Plant Variety Act (LFVV) amending the current (1996), and its relation to the production, trade and supply of seeds in the country. It is related to pressure Mexico to locate legal under the Act 91 of the International Union for the Protection of New Varieties of Plants (UPOV) to establish a legal framework suitable for seed corporations, with the possible authorization for commercial plantings transgenic maize and if, upon the occurrence of contamination of native maize and improved proprietary national events polluting any normal maize enforce their patent rights and to demand royalty payments. The seed law dictates that all varieties (improved or native) is incorporated in the National Catalogue of Plant Varieties (CNVV) as a prerequisite to enter the qualification process, for which it must rely on the characterization based on the Technical Guide for the Maize Varietal description, complicating management and criminalizes ancient seed maize growers.
Keywords: variety protection; patents; seed production; genetically modified organisms